Estimating the Need for Hospital Beds in Bushehr Province, Focusing on Treatment Poles: a Prospective Study to 2032 - Habib Omranikhoo; Alireza Raeisi; Amir hossein Darabi; Mahdi Rezaee (Iranian South Medical Journal)
Background: The success of any organization lies in planning, outlining goals, and charting the path to achieve them. The aim of this study was to develop a treatment roadmap for Bushehr province, with a particular focus on the estimation of required hospital beds using the innovative approach called “treatment poles” up to the year 2032. Materials and Methods: This is a prospective study that uses basic assumptions, current performance indicators, expert opinions and the geography of the province to separately estimate the required hospital beds within three groups of active, special and outpatient beds for the three geographical regions of the province –the so-called “treatment poles”. Results: The results indicate that by 2032, the number of beds and their ratio (beds to population per thousand people) in the province, including active beds, total beds, outpatient beds and special beds, will reach 3520 (2.29), 4483 (2.92), 963 (0.63) and 394 (0.26), respectively. Also, the participation of medical service providers in the province, including public sector (university), non-government public sector (social security), non-academic government sector (oil/armed forces), charity and private sector will be distributed as 65.66, 12.39, 3.92, 6.81 and 10.23 percent, respectively. Conclusion: The findings indicate that the implementation of this methodology can facilitate a more equitable allocation of medical resources and enhance accessibility to health care services across diverse geographical regions within the province. The findings of this research can assist policymakers in making more informed decisions regarding the development of medical infrastructure in Bushehr province.